Philosophical analysis of the theoretical foundations of the study of religious mysticism (Journal of Philosophy Culture and Political Science, 2018)
This article is devoted to philosophical reflection on the theoretical base of the modern study of religious mysticism, which makes new forms of social dialogue and communication. The authors reveal features of mystical component in the modern religious traditions. Notes, that mysticism is not the only a special form of relations, but it is substantive tradition in the system of spiritual culture, the foundation of which is the “mystical experience”. Expansion the scope of non-traditional religious mysticism causes necessity of analysis that phenomenon and requires more complete information of the issue. Key words: religion, mysticism, religious mysticism, mystical consciousness.